PICOSEC Micromegas precise-timing detectors: development towards large-area application and integration - Meng, Y.; Aleksan, R.; Angelis, Y.; Bortfeldt, J.; Brunbauer, F.; Brunoldi, M.; Chatzianagnostou, E.; Datta, J.; Degmelt, K.; Fanourakis, G.; Fiorina, D.; Floethner, K. J.; et al. (Journal of Instrumentation, 2025)
PICOSEC Micromegas (MM) is a precise timing gaseous detector based on a Cherenkov radiator coupled with a semi-transparent photocathode and an MM amplifying structure. The detector concept was successfully demonstrated through a single-channel prototype, achieving sub-25 ps time resolution with Minimum Ionizing Particles (MIPs). A series of studies followed, aimed at developing robust, large-area, and scalable detectors with high time resolution, complemented by specialized fast-response readout electronics. This work presents recent advancements towards large-area resistive PICOSEC MM, including 10 × 10 cm2 area prototypes and a 20 × 20 cm2 prototype, which features the jointing of four photocathodes. The time resolution of these detector prototypes was tested during the test beam, achieved a timing performance of around 25 ps for individual pads in MIPs. Meanwhile, customized electronics have been developed dedicated to the high-precision time measurement of the large-area PICOSEC MM. The performance of the entire system was evaluated during the test beam, demonstrating its capability for large-area integration. These advancements highlight the potential of PICOSEC MM to meet the stringent requirements of future particle physics experiments.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Cherenkov detectors; Micropattern gaseous detectors (MSGC; GEM; THGEM; RETHGEM; MHSP; MICROPIC; MICROMEGAS; InGrid; etc); Timing detectors